STUDENT PERSPECTIVES ON ESSENTIAL SKILLS FOR WORK-INTEGRATED LEARNING IN TOURISM MANAGEMENT: AN EMPIRICAL STUDY - Kenneth, Mealine; Sucheran, Reshma (International Online Journal of Education and Teaching, 2025)
In South Africa, the tourism industry has experienced rapid growth, creating a demand for professionally trained personnel. Higher education institutions (HEIs) have introduced specialised tourism qualifications to address this need. Furthermore, the South African government has stressed the importance of skills development and enhancing educational quality. HEIs integrate Work Integrated Learning (WIL) programs into tourism curricula to develop students’ industry readiness. This study evaluates the tourism management curriculum at a South African University of Technology (UoT) and its influence on the WIL experience of students enrolled in the National Diploma in Tourism Management between 2015 and 2019. Utilising a quantitative research approach, data were collected through a structured online questionnaire distributed to a sample of 106 graduates selected via non-probability sampling. Findings indicate that DUT’s tourism management curriculum effectively equips students with essential skills through active industry engagement. However, graduates reported a gap in technological training, particularly in tourism management systems, which they identified as critical for efficient operational performance within the tourism sector. The study results highlight areas for curriculum enhancement to better align educational outcomes with industry requirements.